Penerapan Pendekatan Holistik dalam Pembelajaran Bahasa Arab di Pondok Pesantren Bustanul Ulum Ketanggungan Brebes - Mohamad Maftuh Fauzi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research analyzes the application of a holistic approach in teaching Arabic at Pondok Pesantren Bustanul Ulum Ketanggungan Brebes. The holistic approach emphasizes the integration of knowledge, feelings, and physical skills to improve students' overall Arabic language proficiency.This research uses a descriptive qualitative method with data collection techniques such as observation, interviews, and document collection. The subjects of the research include Arabic language teachers, students, and educational staff involved in the teaching and learning activities. Data is analyzed through the steps of data reduction, data presentation, and conclusion drawing.The research results show that a holistic approach is implemented through project-based learning, group discussions, and the use of audio-visual media. The main supporting factors include the active role of teachers in guiding and motivating students, a comfortable learning atmosphere, and the availability of various learning media. However, there are challenges such as the lack of available teaching time and the differences in students' abilities to understand the material being taught. However, a holistic approach has proven successful in improving students' Arabic language skills if supported by appropriate teaching methods that meet their needs. This research recommends strengthening the role of teachers in the teaching and learning process, optimizing the use of learning resources, and developing flexible strategies to enhance the effectiveness of Arabic language learning in the future.